VOCABULARY ENHANCEMENT USING CROSSWORD PUZZLE (WORD LINK) & GTM - Caroline Victorine Katemba (Eternal (English, Teaching, Learning & Research Journal), 2023)
One aspect of English is vocabulary. Vocabulary is needed to be able to function well in the four skills (listening, speaking, reading, and writing) of learning language many of the teaching methods created to teach the English language have been included in vocabulary teaching, and it serves the same aims as previous methods. One of the methods that teachers in Indonesia can utilize is the Grammar Translation Method (GTM).  Furthermore, the researcher uses the Word Link app as an example of a crossword puzzle game on a mobile device. Grammar Translation Method (GTM) is one of the methods that can be used by teachers in Indonesia. In addition, the researcher use the Word Link application as an example of a crossword puzzle game mobile application. The focus of this research is to see whether the Grammar Translation Method (GTM) using the Word Link application will enhance students' vocabulary. The pre-experimental group consisted of 25 students from Karya Utama elementary school grade 5. A pre-test was conducted at the beginning of the program followed by a post-test at the end of the 32 hours meeting program. Meetings are held twice per week. Based on the research results, it showed that applying GTM using the Word Link application gives a positive significant effect in improving students' vocabulary. It indicates that the crossword puzzle helps students improve their vocabulary, and it is also recommended that teachers employ this strategy in the English teaching and learning process, particularly in elementary school.